Effect of stressed-skin action on optimal design of cold-formed steel square and rectangular-shaped portal frame buildings - Wrzesien, A.; Phan, D.; Lim, J.; Lau, Hieng Ho; Hajirasouliha, I.; Tan, C. (2016)
© 2016, Korean Society of Steel Construction and Springer-Verlag Berlin Heidelberg.Cold-formed steel (CFS) portal frames can be a viable alternative to conventional hot-rolled steel portal frames. They are commonly used for low-rise commercial, light industrial and agricultural buildings. In this paper, the effect of stressed-skin action on the optimum design of CFS portal frames is investigated by conducting a minimum cost design optimisation on a building of span of 6 m, height-to-eaves of 3 m and frame spacing of 3 m; the effect of different number of bays are considered. For the purpose of this study, it is assumed that gables are rigid.The effect of stressed-skin action is larger for“square-shaped” buildings (i.e. when the span and length are the same on plan) and decreases as more bays are added(i.e. as the building becomes more “rectangular-shaped” on plan). The results of the minimum cost optimisation indicate that if stressed-skin action is taken into account, the cost of the internal frame can be reduced by around half for “square-shaped” buildings. It should be noted that this is a minimum cost optimisation, which is not the same as a minimum weight optimisation. It is also shown that a safe design of internal frames could be obtained by ignoring wind loads (i.e. designing the frame only for gravity loads),but this is limited to buildings having a “square-shape”.